Pengaruh Job Insecurity terhadap Kesejahteraan Psikologis dengan Social Support sebagai Variabel Moderator pada Karyawan Outsourcing di PT Pegadaian Area Padang - Pratama, Genta Putra; Guspa, Anindra (YASIN, 2024)
The objectives of this study are 3, namely, 1) Knowing how the level of job insecurity experienced by employees. 2) To test whether there is an effect of job insecurity on psychological well-being in employees. 3) To find out how social support acts as a moderator variable in reducing the negative impact of job insecurity on psychological well-being. In this study, researchers used the simple random sampling method for sampling from the population. With the number of samples taken around 120 people. This study uses simple linear regression techniques in the data analysis process. This technique is used to identify the influence between job insecurity and social support on psychological well-being. Based on the results of data analysis that has been carried out and the discussion as described in the previous chapter, three conclusions can be drawn from this study. First, Job Insecurity has a positive and significant effect on Psychological Wellbeing, so H1 is rejected. Second, Social Support has a significant effect on Psychological Wellbeing but has a negative distribution, meaning that Social Support has an indirect effect on Psychological Wellbeing, so H2 is rejected. Third, Social Support moderates the effect of Job Insecurity on Psychological Wellbeing, so H3 is accepted.